Prospects of Employment Generation & Industrial Production: A Study of Small-Scale Industries in Pakistan - Haq, Naveed ul; Nazir, Muhammad Kashif (Journal of Public Policy Practitioners, 2025)
The industrial sector is of great importance to the development of a country. Historically, countries with strong industrial sectors have experienced greater economic growth and development. In Pakistan, Punjab has done remarkably well in agriculture and has also made significant progress in industrialization by developing small, medium, and large-scale industries. Among these sectors, small-scale industries (SSIs) are pivotal in the overall added industrial value and employment generation. The significance of this sector can be assessed from the fact that it alone absorbs nearly 60% of the employment of the industrial sector and contributes about 58% of the overall industrial production of Punjab. In this regard, the present study examines the determinants of employment and industrial production in small-scale industries in Punjab, Pakistan. The study employed the firm’s level, cross-sectional data collected from a census of small and cottage industries of Punjab, carried out by Punjab Small Industries Corporation in collaboration with the Bureau of Statistics, Punjab, in the 36 districts of Punjab during 2011-13. To estimate the determinants of employment and industrial production, the two-stage least squares (2SLS) regression analysis and structural equation modelling (SEM) analysis techniques have been used. The empirical findings are beneficial in identifying the significance of each determinant for better industrial production and employment generation in Punjab. Moreover, the policy implications have also been suggested based on empirical findings.